Postoperative seizure and developmental outcomes of children with hemimegalencephaly and drug-resistant epilepsy. (November 2021) - Liu, Qingzhu; Ma, Jiayi; Yu, Guojing; Zhang, Qian; Zhu, Ying; Wang, Ruofan; Yu, Hao; Liu, Chang; Sun, Yu; Wang, Wen; Wang, Shuang; Ji, Taoyun; et al.
Highlights: For children with HMEG, the predicted probability of being seizure-free three years after surgery was 79.4%. For children with HMEG, the percentage of catch-up, stabilization and regression in both short and long-term DQ after surgery was approximately 40%, 35% and 25%, respectively. Change of DQ shortly after surgery might predict the long-term developmental outcome indicating the importance of short-term developmental assessment. Abstract: Objective: To evaluate seizure and developmental outcomes in the short and long term in children with hemimegalencephaly (HMEG) after surgery. Methods: This is a cohort study of 36 children who underwent surgery for HMEG were followed up for at least 1 year postoperatively. The Griffiths Mental Development Scales, Ages and Stages Questionnaire version 3, and Peabody Developmental Motor Scales were used to assess development. Results: The median postoperative follow-up duration was 2.7 (1.0–5.0) years, and median age at surgery was 1.9 years (5.8 months-5.9 years). At the last follow-up, 83% of children were seizure-free. the predicted probability of being seizure-free three years after surgery was 79%. The proportion of patients who were moderate to severe delay declined from 97% preoperatively to 76% at least 1 year after surgery. Catch-up, stabilization, and regression of developmental quotient (DQ) was observed in 41%, 35%, and 24% of children 3 months after surgery, respectively. The corresponding proportions during long-term follow-up were 40%, 33%, and 27%, respectively. Change of DQ shortly after surgery was negatively correlated with age at seizure onset and age at surgery. The long-term DQ was positively correlated with the preoperative DQ. Long-term change of DQ was positively correlated with change of DQ shortly after surgery. Conclusions: Most of patients with HMEG could achieve seizure free after surgery. After surgery, the proportion of catch-up, stabilization, and regression in both short- and long-term DQ was approximately 40%, 35%, and 25%, respectively. The change of DQ shortly after surgery may be a predictor for long-term developmental change.